COMPLICATIONS AND SAFETY OF POST PERCUTANEOUS RENAL BIOPSY SHORT STAY IN PAEDIATRIC PATIENTS - Shah, Syed Sajid Hussain; Akhtar, Naureen; Ahmed, Tausif; Sunbleen, Faiza (Journal of Ayub Medical College Abbottabad, 2015)
Background: Renal biopsy is gold standard in diagnosis of various renal diseases. Though it is safe yet it requires adequate patient evaluation, preparation and monitoring after the procedure. Methods: This descriptive case series was conducted in the Paediatric Nephrology Department, The Children’s Hospital Lahore over a period of one year. Children aged less than 16 years were included who were suffering from renal diseases requiring renal biopsy for diagnosis. After renal biopsy patients were monitored for complications and were discharged after short stay of eight hours who got no complication during the observation period. Results: Out of total 145 patients, 97 (66.1%) were males and 48 (33.9%) were females. The age range was from 0.7 years to 16 years. The duration of stay after renal biopsy was up to eight hours in 131 (90.34%) patients, while 14 (9.66%) stayed longer. Post-biopsy stay of 24 hours was observed in 8 patients and 48 hours in 5 patients. Only 1 patient stayed for 96 hours. Patients with gross haematuria were 6 (4.1%) who were checked for perinephric hematoma formation by ultrasonography. Only one patient required blood transfusion along with fresh frozen plasma. The most common histopathological diagnosis was Mesangioproliferative with 67(46.2%) cases, followed by Glomerulonephritis in 35(24.1%) patients having Membranoproliferative Glomerulonephritis (MPGN) while Systemic Lupus Erythematous (SLE) nephritis was reported in 15 (10.35%) patients. Conclusion: Patients can be discharged after short stay post renal biopsy procedure provided done after proper screening of patients. As it not only reduces patient stay but also is cost effective. Keywords: Renal Biopsy, short stay, haematuria, complications